Perlindungan Hukum Terhadap Anak Sebagai Korban Tindak Pidana Pemerkosaan - Er Tanjung; Lusia Sulastri; Rabiah Al Adawiah (Jurnal Hukum Sasana, 2023)
The worrying crime of rape is a crime where the victim is still a minor. The perpetrators must be severely punished because they have damaged the future of the child and can even cause psychological harm to the child's development. Children who experience the crime of sexual intercourse can experience deep trauma as well as psychological and physical disorders because in essence the child must be protected. The research objectives to be achieved are to determine the legal protection efforts for children who are victims of criminal acts of rape and to determine the criminal responsibility of perpetrators of raping against minors. This study uses normative research because this research describes the existing problems to be further discussed with a study of applicable legal theories. The results of this study indicate that legal protection efforts against children who are victims of criminal acts of rape are still lacking. The protection carried out is only limited to giving appropriate punishments to the perpetrators, even according to the author the punishments given are not commensurate with the perpetrators, while children as victims who suffer both material and immaterial losses have not received attention at all.